GABA receptors in the olfactory epithelium of the gilthead seabream (Sparus aurata) - Costa, Rita (2022)
Exposure to high PCO2/low pH seawater induces behavioural alterations in fish; a possible explanation for this is a reversal of Cl-/HCO3- currents through GABAA receptors (the GABAA receptor theory). However, the main evidence for this is that gabazine, a GABAA receptor antagonist, reverses these effects when applied to the water, assuming that exposure to systems other than the CNS would be without effect. Here, we show the expression of both metabotropic and ionotropic GABA receptors, and the presence of GABAA receptor protein, in the olfactory epithelium of gilthead seabream. Furthermore, exposure of the olfactory epithelium to muscimol (a specific GABAA receptor agonist) increases or decreases the apparent olfactory sensitivity to some odorants. Thus, although the exact function of GABAA receptors in the olfactory epithelium is not yet clear, this may complicate the interpretation of studies wherein water-borne gabazine is used to reverse the effects of high CO2 levels on olfactory-driven behaviour in fish.